Comparative analysis of ensiling characteristics and protein degradation of alfalfa silage prepared with corn or sweet sorghum in semiarid region of Inner Mongolia. (27th November 2019) - Tao, Ya; Sun, Qizhong; Li, Feng; Xu, Chuncheng; Cai, Yimin
Abstract: This study was conducted to evaluate silage fermentation and protein degradation of alfalfa prepared with corn or sweet sorghum (SS) at different mixing ratios. The chemical composition, ensiling characteristics, and protein degradation of alfalfa prepared with and without corn or SS at mixing ratios of 7:3, 1:1, and 3:7 on a fresh matter (FM) basis were studied. The alfalfa had the highest crude protein (CP) content and lactate buffering capacity (LBC), but lower water‐soluble carbohydrate (WSC) content than corn and SS. After 60 days of ensiling, the corn and SS silages had good quality, with lower pH and ammonia‐N content, and higher dry matter (DM) content than the alfalfa silages. In the alfalfa and corn mixture silages, the DM contents linearly increased with an increase in the proportion of corn, while the pH, non‐protein N (NPN), ammonia‐N, and peptide‐N contents linearly decreased. In the alfalfa and SS mixture silages, the DM and NPN contents linearly increased with an increase in the proportion of SS, while the pH, lactic acid, and ammonia‐N contents linearly decreased. This study suggests that alfalfa silage prepared with corn has more positive effect on fermentation quality and inhibiting protein degradation than addition of SS.